X-ray diffraction studies of residual strain in AlN/sapphire templates. (15th August 2022) - Serafinczuk, J.; Pawlaczyk, L.; Moszak, K.; Pucicki, D.; Kudrawiec, R.; Hommel, D.
Abstract: The residual strain in the templates can significantly influence the properties of heterostructures grown on these templates and this issue cannot be neglected in e.g. LED applications. In this paper, we present an approach to determine the residual strain in AlN/sapphire templates using X-ray diffractometry at edge scans geometry. It is based on measurements carried out both: from the surface and from the edge of the sample. Edge scans allow measurements of planes perpendicular to the growth direction, which permit the unambiguous determination of the in-plane strain. This approach facilitates the characterization of AlN structures. The use of edge scans allows determining directly in-plane a lattice parameter on which the analysis is based. The reference values of the AlN lattice parameters were determined experimentally from the AlN bulk crystal. Highlights: The in-plane residual strain in AlN/sapphire templates can be determined using X-ray diffractometry at the edge scans geometry. The XRD measurements from the edge of the sample allow for direct determination of the lattice parameter a . The presence of residual strains in the AlN template layers is mainly a derivative of dislocations.